Perlindungan Hukum Bagi Korban Tindak PidanaKekerasan Yang Menimbulkan Cacat Tetap( Studi kasus di Pengadilan Negeri Surakarta ) - Kusuma, Aswin Hendra, Hartanto, S.H., M.Hum (2017)
Protection laws applied in Indonesia is currently less attention to the interests of the victims are in dire need of legal protection. Many. cases often occur in the community, especially in cases of crimes of violence is in need of legal protection for victims. Law enforcement officials pay less attention to the interests of victims who have suffered as a result of criminal acts that have happened to him. The importance of legal protection for victims of criminal acts could alleviate the conditions for the victims who have already suffered. Victims who suffered violence and even cause permanent disabilities need the protection of the law for criminal acts which cause suffering and loss for the victim. Keep in mind the extent to which victims obtain legal protection as expected due to the actions of others. Anyt hing that can alleviate the suffering that has been experienced by the victim of someone who referred to the protection of victims.